Full Conjugate Contour Constructing of Helical Rotor with Higher and Its Flow Ripple Formula - Taixi Quan; Yan Yang (Jixie chuandong)
To efficiently realize lightweight and low flow pulsation performance for helical rotor pump. Firstly， a new helical rotor with only three lobes and a full conjugate contour for higher shape factor is presented， then， from taking dimensionless theoretical flow formula of its homologous straight rotor as a integrand function， the exact formula of dimensionless theoretical flow and following flow ripple factor of the new helical rotor are deduced. Finally， from results analysis of flow ripple factor of involute， circular and cycloid as three different contour type， a general simplified formula of flow ripple factor for the new helical rotor is obtained. The results show that instantaneous diameter as representing contour type has good universality， dimensionless derivation process of theoretical flow is simple and reliable. Flow ripple factor of the new helical rotor has a very approximate negative linear variation law with helical angle， which can be attributed to flow ripple factor of its homologous straight rotor and is a concise function of helical angle， contour factor， shape factor. The curve type of rotor contour has little influence on flow ripple factor， and simplified error of fixed impact factor of 1.05 is less than 3%. Three helical lobes with 60° helical angle is the best contour structures without flow ripple， the full conjugate structure of end contour can effectively reduce leakage in conjugate zone of rotor pair， etc. The results provide a basis for further development of lightweight helical rotor pump.